Development of visualized earned value management tool for project management - Abdullah, Andy-Al-Affendi (2018)
This research presents an application framework named, Visualized Earned Value Management System (VEVM) for assessing project performance along initiation, planning, execution and closure phases by deploying earned value (EV) analysis and possible integration with existing project management database system. The existing system is named as Electronic Project Status Report (ePSR) which developed by Continental Ag. First part of this study was to evaluate the acceptance among project management practisioner on earned value management method thru conducted survey. This study also attempts to solve problem and promote EV to project manager and project stake holder in handling complicated, dynamic and massive project information especially when changes to the project baseline which is unavoidable. Thus, it is crucial for a project manager to have a comprehensive yet simple system to use in order to assist project manager in managing these deviations to ensure project are kept in the plan path and complying to the triple constraints in project management which are time, cost and scope. This research contributed on development of VEVM in order to provide graphical information about the project status which also serves as a control technique to monitor the project status on cost control, schedule performance and to provide early alert for corrective action on highlighted deviation from the project baseline. Through feasibility study, it has been shown that the visualized system provide an objective measures of the work that project manager can access project achievement by converting the project data into manageable information clusters and in parallel promoting the earned value management method as an effective tool to monitor and control project constraints which are cost, timeline and scope. Analysis based on project actual data used , showed that the developed visualized EVM tool is able to provide project actual and forecast trend status in term of execution as early as G30 phase on the development PLC. The problem faced claimed by project management practioner such as EVM is a complicated tool to understand and taking too much time to manage are overcome with usage of the developed visualized earned value management system. The graphical information and triggering features in the sdeveloped tool provides quick and easy understanding of the project health at various stages of the project-life-cycle.